2015
DOI: 10.3892/or.2015.3821
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-494 promotes cervical cancer proliferation through the regulation of PTEN

Abstract: The phosphoinositide 3-kinase (PI3K)/Akt signaling pathway appears to be a key regulator in cervical carcinogenesis. The phosphatase and tensin homolog deleted on chromosome 10 (PTEN) protein is principally involved in the homeostatic maintenance of PI3K/Akt signaling and PTEN has been identified to play an important role in the occurrence and development of cervical cancer. MicroRNA (miRNA)-494 has been proven to be involved in the carcinogenesis and development of various types of cancer by directly targetin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 44 publications
1
36
2
Order By: Relevance
“…Contrary to our finding of it being suppressed in BCC relative to SCC and HK, miR-494 is induced in several cancers (malignant breast cancer, esophageal squamous cell carcinoma, gastric carcinoma, oral cancer, ovarian cancer and pancreatic cancer) (148)(149)(150)(151)(152)(153)(154)(155)(156)(157). Rather than inferring its suppression in BCC, perhaps it is induced early in the transformation of keratinocytes to SCC.…”
Section: A Study Population Demographics and Histopathological Analysiscontrasting
confidence: 99%
“…Contrary to our finding of it being suppressed in BCC relative to SCC and HK, miR-494 is induced in several cancers (malignant breast cancer, esophageal squamous cell carcinoma, gastric carcinoma, oral cancer, ovarian cancer and pancreatic cancer) (148)(149)(150)(151)(152)(153)(154)(155)(156)(157). Rather than inferring its suppression in BCC, perhaps it is induced early in the transformation of keratinocytes to SCC.…”
Section: A Study Population Demographics and Histopathological Analysiscontrasting
confidence: 99%
“…Previous studies have identified that miR-494 is associated with the development of tumors (8,9). However, there are a limited number of studies on the expression and the function of miR-494 in cervical cancer.…”
Section: Mir-494 Expression Is Associated With Clinicopathological Fementioning
confidence: 99%
“…Previous studies have revealed abnormal expression of a number of miRNAs in cervical cancer, including miR-214, miR-21, miR-143 and miR-145 (4-7). In cervical cancer, miR-214 expression is decreased, which has been reported to inhibit cancer progression through targeting mitochondrial transcription factor A (8). miR-21 overexpression may inhibit the expression of phosphatase and tensin homolog (PTEN), and promote cancer cell proliferation and migration (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been performed on the role and related mechanism of miRNAs in numerous different kinds of diseases (9)(10)(11)(12). miRNAs bind primarily to the 3'-untranslated region (3'UTR) of their target messenger RNAs (mRNAs) to reduce their stability and decrease the expression of target mRNAs at the post-transcriptional level (13), which play important roles in various biological processes including cell growth, proliferation, differentiation and death (14)(15)(16)(17)(18)(19). Concerning chemotherapy in various types of cancers such as breast cancer, lung adenocarcinoma, glioblastoma, and ovarian cancer, recent studies have shown that miRNAs also act in important roles (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%